Current, emerging and potential pest threats to Sitka spruce plantations and the role of pest risk analysis in preventing new pest introductions to Ireland. (25th October 2018) - Tuffen, Melanie G; Grogan, Helen M
Abstract: Sitka spruce ( Picea sitchensis ) is the predominant tree species used in Irish forestry, comprising over 50 per cent of the forest estate. The island of Ireland is free of many of the most damaging pests and diseases of spruce present in Europe, and consequently forest stands of Sitka spruce are generally healthy and productive. FORM is a research project with the aim to enhance productivity and pest and disease resistance to key forest species in Ireland. It includes a work package to identify and risk analyse threats to Sitka spruce. A global pest list of spruce was compiled and identified over 1000 pests and potential pests of spruce. Using the pest list as a starting point, this review examines the major pests of Sitka spruce both in its native range in the Pacific Northwest of North America and within Europe where it is grown as an exotic. It also reviews emerging pests and diseases of spruces in general that may threaten Sitka spruce plantations in Ireland. Details of how pest risk analysis of these threats can aid in their continued exclusion are discussed.